Between market economy and state capitalism China's state-owned enterprises and the world trading system - Gao, Henry ca. 20./21. Jh; Zhou, Weihuan 1981- (Cambridge international trade and economic law, 2023)
One major issue facing the world trading system today is how to deal with the challenge of China's state capitalism. Many commentators believe that the existing WTO rules are insufficient and, thus new rules are needed. This book challenges this conventional wisdom. Through meticulous studies and fresh analysis of the commitments in China's WTO accession package, existing rules on state capitalism in WTO agreements and recent attempts to make new rules on these issues at the bilateral, regional and multilateral levels, this book argues that existing WTO rules, especially those on subsidies, coupled with China-specific rules in its accession protocol, do provide feasible tools to counter China's state capitalism. This book also discusses the reasons for the lack of usage of these rules and provides concrete policy suggestions on how the rules may be better utilized, as well as how to conduct constructive negotiations on new rules in the WTO and beyond